Low Copper Diet-A Therapeutic Option for Wilson Disease? - Ulrike Teufel-Schäfer; Christine Forster; Nikolaus Schaefer (MDPI AG, 2022)
Wilson's disease (WD) is an autosomal recessive inherited disease in which a pathological storage of copper in various organs is the mean pathophysiological mechanism. The therapy consists of drug therapy with chelating agents or zinc. For patients, nutrition is always an important issue. The aim of this review was to determine whether there are clear recommendations for a low copper diet for WD patients, or whether the essential trace element zinc plays a role? We were able to show that some of the foods with high copper content would have to be consumed in such large quantities that this is regularly not the case. Furthermore, there are also different absorption rates depending on the copper content. A lower copper intake only prevents the re-accumulation of copper. In summary, consistent adherence to drug therapy is more important than a strict diet. Only two foods should be consistently avoided: Liver and Shellfish.